2007
DOI: 10.1159/000097965
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Continuity between Bipolar and Depressive Disorders?

Abstract: Background: Recent studies questioned the current categorical split of mood disorders into bipolar disorders (BP) and depressive disorders (MDD). Methods: Medline database search of papers from the last 10 years on the categorical-dimensional classification of mood disorders. Various combinations of the following key words were used: mood disorders, bipolar, unipolar, major depressive disorder, spectrum, category/categorical, classification, continuity. Only English language clinical papers were included, revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 165 publications
2
36
0
1
Order By: Relevance
“…Recent data demonstrate convincingly that DSM-IV diagnoses may not necessarily be pathophysiologically distinct: there is considerable genetic overlap between BD and schizophrenia 27 and between BD and MDD. 28 As noted, BD and SMD appear to share pathophysiological mechanisms, making it possible that the SMD phenotype will ultimately be placed on a pathophysiological spectrum between BD and MDD and/or other depressive syndromes. Accordingly, we found that depressive episodes were significantly more common in the BD group; a possible post hoc explanation for this finding is that, consistent with previous data, 10 SMD may be linked with depressive phenotypes not characterized by episodicity, such as dysthymia.…”
Section: Discussionmentioning
confidence: 97%
“…Recent data demonstrate convincingly that DSM-IV diagnoses may not necessarily be pathophysiologically distinct: there is considerable genetic overlap between BD and schizophrenia 27 and between BD and MDD. 28 As noted, BD and SMD appear to share pathophysiological mechanisms, making it possible that the SMD phenotype will ultimately be placed on a pathophysiological spectrum between BD and MDD and/or other depressive syndromes. Accordingly, we found that depressive episodes were significantly more common in the BD group; a possible post hoc explanation for this finding is that, consistent with previous data, 10 SMD may be linked with depressive phenotypes not characterized by episodicity, such as dysthymia.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a proportion of patients with MDD can develop manic or hypomanic episodes and become bipolar in the future (Akiskal et al, 1995) or even fit into de concept of 'bipolar spectrum' without showing obvious manic symptomatic polarity (Akiskal and Pinto, 2000). In addition, some clinical data support a unitary conceptualization of MD (Benazzi, 2007;Cassano et al, 2004). However, they differ in several clinical, pathophysiological, and therapeutic features (Ghaemi et al, 2004;Yatham et al, 1997) and independent loci have been reported to be associated with one or other diagnosis (Kato, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical differentiation of such morbidity requires a shift from the current psychometric model (where severity is determined by the number of symptoms and not by intensity or quality) to a clinimetric model [14,15,16], which may allow to define the progression, extent and severity of depressive illness. Finally, emerging evidence from the studies concerned with bipolar disorders [17,18,19,20,21] call for a reassessment of the current categorical split of mood disorders. Benazzi [18] has suggested that, focusing on mood spectrum’s extremes, a categorical distinction seems to be supported.…”
Section: The Inadequacies Of Standard Clinical Assessmentmentioning
confidence: 99%
“…Finally, emerging evidence from the studies concerned with bipolar disorders [17,18,19,20,21] call for a reassessment of the current categorical split of mood disorders. Benazzi [18] has suggested that, focusing on mood spectrum’s extremes, a categorical distinction seems to be supported. Focusing on midway disorders (e.g.…”
Section: The Inadequacies Of Standard Clinical Assessmentmentioning
confidence: 99%